Transcription Factors: The Fulcrum Between Cell Development and Carcinogenesis - Islam, Zeyaul; Ali, Ameena Mohamed; Naik, Adviti; Eldaw, Mohamed; Decock, Julie; Kolatkar, Prasanna R. (Frontiers in Oncology, 2021)
Higher eukaryotic development is a complex and tightly regulated process, whereby transcription factors (TFs) play a key role in controlling the gene regulatory networks. Dysregulation of these regulatory networks has also been associated with carcinogenesis. Transcription factors are key enablers of cancer stemness, which support the maintenance and function of cancer stem cells that are believed to act as seeds for cancer initiation, progression and metastasis, and treatment resistance. One key area of research is to understand how these factors interact and collaborate to define cellular fate during embryogenesis as well as during tumor development. This review focuses on understanding the role of TFs in cell development and cancer. The molecular mechanisms of cell fate decision are of key importance in efforts towards developing better protocols for directed differentiation of cells in research and medicine. We also discuss the dysregulation of TFs and their role in cancer progression and metastasis, exploring TF networks as direct or indirect targets for therapeutic intervention, as well as specific TFs’ potential as biomarkers for predicting and monitoring treatment responses.